APLIKASI BERBAGAI MACAM BIOURINE TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI VARIETAS INPARI IR NUTRI ZINC - Riviken, Mantegna Gordi; Fitriani, Dwi; Podesta, Fiana; Suryadi; Safitri, Isnin Kurnia (University of Prof. Dr. Hazairin, SH, 2024)
The study aims to know the growth and production of rice is the nutrii zinc of applications for various types of urine. The study was conducted in September 2023 at Balai Penerapan Standar Instrumen Pertanian (BPSIP) Bengkulu Irian street km 6.5 Bengkulu City. The reserch was carried out using a Completely Randomized Design (CRD) non-vectorial materials with a type of urine of 4 levels: non biourine (P0); Cow biourine (P1); Rabbit biourine (P2); And goat biourine (P3) by giving each biourine by 10%. Each treatment was repeated six times with a sample of each repetition made up of five units of plants. The results of further analysis on annova are followed by the practice of Duncan's Multipe Range Test (DMRT) at 5 %. Research shows that the increased biomes of urine of cows, rabbits, and goats affect the high parameters of the plant, have a very real impact on the parameters of total number of anteses, and be very effective at the percentage parameters of the contents of rice.